Flutter accessibility suggestion tool (2020)
Flutter Accessibility Suggestion Tool An open-source tool developed using TypeScript language. The purpose of this extension is to facilitate the detection of code enhancements for the creation and maintenance of accessible applications. Its main objective is to allow screen readers to navigate in applications that follow the suggestions of the extension. Additionally, we had planned a coverage for the extension in IDEs such as Android Studio and Visual Studio, but due to time constraints and the pandemic season, we only chose to create an extension for the IDE Visual Studio Code.